Liver-Kidney-on-Chip to study toxicity of drug metabolites - Theobald, Jannick; Ghanem, Ali; Wallisch, Patrick; Cheng, Xinlai; Wölfl, Stefan (ACS biomaterials science & engineering, 2018)
Advances in organ-on-chip technologies for the application in in vitro drug development provide an attractive alternative approach to replace ethically controversial animal testing and to establish a basis for accelerated drug development. In recent years, various chip-based tissue culture systems have been developed, which are mostly optimized for cultivation of one single cell type or organoid structure and lack the representation of multi organ interactions. Here we present an optimized microfluidic chip design consisting of interconnected compartments, which provides the possibility to mimic the exchange between different organ specific cell types and enables to study interdependent cellular responses between organs and demonstrate that such tandem system can greatly improve the reproducibility and efficiency of toxicity studies. In a simplified liver-kidney-on-chip model, we showed that hepatic cells that grow in microfluidic conditions abundantly and stably expressed metabolism-related biomarkers. Moreover, we applied this system for investigating the biotransformation and toxicity of Aflatoxin B1 (AFB1) and Benzoalphapyrene (BαP), as well as the interaction with other chemicals. The results clearly demonstrate that the toxicity and metabolic response to drugs can be evaluated in a flow-dependent manner within our system, supporting the importance of advanced interconnected multiorgans in microfluidic devices for application in in vitro toxicity testing and as optimized tissue culture systems for in vitro drug screening.
Publication Date: November 12, 2017
Gesehen am 05.08.2019